Analysis of phytoplankton abundance in kassikebo waters, pangkep regency, south sulawesi, indonesia - Rahmadi Tambaru; Muh Farid Samawi; Ambo Tuwo; Sulaiman Gosalam; Nur Qalbi Mujahidah (JPBIO (Jurnal Pendidikan Biologi), 2023)
Changes in nutrient concentrations can be caused by anthropogenic activities in coastal and marine waters. This affects the abundance of phytoplankton. The waters experiencing it are the waters of Kassikebo Pangkep, South Sulawesi, Indonesia. For this reason, research has been carried out to analyze the abundance and structure of phytoplankton communities in these waters, from January to July 2022. To identify phytoplankton, 100 L of seawater samples were filtered, which were taken at each station. The results of that water filter, identified in the laboratory. The results showed that the classes of phytoplankton found were Bacillariophyceae and Cyanophyceae. Species found such as Skeletonema and Detonula. The results of One-way ANOVA showed that phytoplankton abundance was not significantly different between observation stations (p>0.05). Changes in phytoplankton abundance are caused by pH.